A gains from trade perspective on macroeconomic fluctuations - Paul Beaudry; Franck Portier (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
Business cycles reflect changes over time in the amount of trade between individuals. In this paper we show that incorporating explicitly intra-temporal gains from trade between individuals into a macroeconomic model can provide new insight into the potential mechanisms driving economic fluctuations as well as modify key policy implications. We first show how a gains from trade approach can easily explain why changes in perceptions about the future (including news about the future and risk shocks) can cause booms and bust. We then turn to fiscal policy, and discuss under what conditions fiscal multipliers can be observed. While much of our analysis is conducted in a flexible price environment, we also present implications of our model for a sticky price environments, as it allows to understand stable-inflation boom-bust cycles. The source of the explicit gains from trade in our setup derives from simply assuming that in the short run workers are not perfect mobile across all sectors of the economy. We provide evidence from the PSID in support of this modeling assumption.
Keywords: E32; 330; business cycle; investment; heterogeneous agents; Konjunktur; Makroökonomischer Einfluss; Handel; Prognose; Wirtschaftspolitik; Theorie